Uncombed, unforeseen, unconstrained - Ardalan, Ziba; Bismuth, Julien 1973-; Morton, Tom 1977- (Mousse Publishing, 2022)
Published in conjunction with the exhibition Uncombed, Unforeseen, Unconstrained, a Collateral Event of the 59th International Art Exhibition | La Biennale di Venezia, 2022, this book documents the deeply thoughtful responses of eleven international contemporary visual artists to the state of the world in the early twenty-first century. Aesthetically beguiling and conceptually convincing, their works reflect on some of the alarming aspects of entropy – often interpreted as the degree of disorder within a system – which are increasingly pervading life on planet Earth and even putting it at risk. Complementing the concept and ideas behind the exhibition, this book includes three thought-provoking texts in the form of two essays: ‘Sensing Time’ by the exhibition’s curator Ziba Ardalan, and ‘Entropisms’ by artist and writer Julien Bismuth; and an intriguingly relevant story by curator and writer Tom Morton
Impressum: This book is published on the occasion of the Parasol unit foundation for contemporary art exhibition "Uncombed, Unforeseen, Unconstrained", 23 April - 27 November 2022, Conservatorio di Musica Benedetto Marcello. A Collateral Event of the 59th International Art Exhibition La Biennale di Venezia
Titelzusatz auf dem Cover: Darren Almond, Oliver Beer, Rana Begum with Hyetal, Julian Charrière, David Claerbout, Bharti Kher, Arghavan Khosravi, Teresa Margolles, Si On, Martin Puryear, and Rayyane Tabet
Keywords: Beer, Oliver -- 1985-; Margolles, Teresa -- 1963-; Begum, Rana -- 1977-; On, Si -- 1979-; Almond, Darren -- 1971-; Puryear, Martin -- 1941-; Kher, Bharti -- 1969-; Claerbout, David -- 1969-; Tabet, Rayyane -- 1983-; Charrière, Julian -- 1987-; Khosravi, Arghavan -- 1984-; Biennale di Venezia -- 59. -- 2022 -- Venedig; Geschichte 2022; Kunst; Ausstellungskatalog -- Conservatorio di Musica Benedetto Marcello -- 23.04.2022-27.11.2022 -- Venedig